COHESIVE STRENGTH OF DENTIN RESISTÊNCIA COESIVA DA DENTINA - DEMARCO,Flávio Fernando (1997)
The bond strength of dentin adhesives to dentin has increased after each generation. Although dentin substratum is part of the bonding process, little importance has been given to measure dentin cohesive strength. The aim of this study was to evaluate the cohesive strength of dentin in human canines. Seventeen non carious canines were selected. All of them had been extracted for more than one year. The teeth were ground until dentin square samples with approximately 2 X 2 mm were obtained. They were embedded in acrylic resin and subjected to shear stress, in a Wolpert Machine, at a crosshead speed of 0.5 mm/min. The mean cohesive strength of dentin in shear mode was 33.95 (+-9.72) MPa. The fracture surfaces were observed under a X40 magnification. A finite element analysis was performed to observe the stress distribution as related to the shear test. The failure pattern was compatible with the shear test and also with the stress distribution in the finite element analysis